2007
DOI: 10.1074/jbc.m610069200
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Structural Insights into the p97-Npl4-Ufd1 Interface

Abstract: The AAA ATPase, p97, achieves its versatility through binding to a wide range of cofactor proteins that adapt it to different cellular functions. The heterodimer UN (comprising Ufd1 and Npl4) is an adaptor complex that recruits p97 for numerous tasks, many of which involve the ubiquitin pathway. Insights into the structural specificity of p97 for its UN adaptor are currently negligible. Here, we present the solution structure of the Npl4 "ubiquitin-like" domain (UBD), which adopts a ␤-grasp fold with a 3 10 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 34 publications
5
74
0
Order By: Relevance
“…Currently, only limited structural information on the SHP box-p97 interaction is available, and the exact binding site of the SHP box on the p97 N domain remains unclear. While NMR data suggest that the binding region of the SHP box of UFD1 on the N domain partially overlaps with the binding site for the UBXL domain of NPL4 [59], pull-down experiments demonstrated that SHP box binding to p97 does not interfere with the binding of UBX/UBXL domains, suggesting different binding sites [50].…”
Section: Shp Box/bs1mentioning
confidence: 93%
See 1 more Smart Citation
“…Currently, only limited structural information on the SHP box-p97 interaction is available, and the exact binding site of the SHP box on the p97 N domain remains unclear. While NMR data suggest that the binding region of the SHP box of UFD1 on the N domain partially overlaps with the binding site for the UBXL domain of NPL4 [59], pull-down experiments demonstrated that SHP box binding to p97 does not interfere with the binding of UBX/UBXL domains, suggesting different binding sites [50].…”
Section: Shp Box/bs1mentioning
confidence: 93%
“…The structure of the UBXL domain of NPL4 has been solved by NMR, and based on chemical shift perturbation analysis a structural model for the N domainÀUBXL complex has been calculated [59] (Fig. 2B).…”
Section: Ubx and Ubxl Domainsmentioning
confidence: 99%
“…2). One of the best-studied adaptors is the heterodimer Ufd1-Npl4, the only essential cofactor in yeast (3)(4)(5)(6), which directs p97 into cellular processes regulated by ubiquitin-proteasome degradation such as endoplasmic reticulum-associated degradation (ERAD) (7)(8)(9)(10), mitotic progression (11,12), replication (13), and transcription factor activation (14,15). In ERAD (16), mitosis (17), and nucleus reformation (12), the p97-Ufd1-Npl4 complex has been shown to recognize ubiquitylated substrates associated with different cellular structures and, with the energy obtained from the binding and/or hydrolysis of ATP, to extract them into the cytosol to be recycled after deubiquitylation or degraded by the proteasome (10,16,18,19).…”
mentioning
confidence: 99%
“…Ufd1 comprises an N-terminal domain, structurally similar to the N domain of p97 and contains binding sites for both poly-and mono-ubiquitin (37), and a flexible C-terminal domain. The structure of Npl4 is less well understood although two domains, the N-terminal ubiquitin-like (UBX-like) domain and the C-terminal NZF (zinc finger), have been solved by NMR (6,25). The interaction between Ufd1-Npl4 and p97 has been described as bipartite with two different p97-interacting sites located at the C-terminal domain of Ufd1 and the UBX-like domain of Npl4 (4), and it has been proposed that these sites interact with two different p97 N domains (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation